Pengaruh Pajak Daerah, Retribusi Daerah, Dan Lain-Lain Pendapatan Asli Daerah Yang Sah Terhadap Pendapatan Asli Daerah Pada Badan Pendapatan Daerah Provinsi Lampung Tahun 2019-2023 - Annisa Maya Ivanka; Meita Sekar Sari; Yulistina Yulistina (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to determine the influence of regional taxes, regional levies and other legitimate regional original income on the original blood income of Lampung Province. The method used in this research is quantitative descriptive and uses secondary data. The number of samples is 60 using the non-probability, time series method, namely the Target and Realization Income Report for Lampung Province for 2019-2023. The analysis technique uses the classic assumption test, multiple linear regression test and hypothesis testing. Based on the results of the analysis, it can be concluded that simultaneously regional taxes, regional levies and other legitimate local original income have a positive and significant effect on local original income, and partially regional taxes and other local original income have a positive and significant effect. The regional levy variabel shows that regional levies do not have a significant and negative effect on local original income.